2014
DOI: 10.1016/j.avsg.2014.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Therapy is Effective Treatment for Focal Stenoses in Failing Infrapopliteal Vein Grafts

Abstract: Objective To evaluate the efficacy of endovascular therapy for maintaining patency and preserving limbs among patients with failing infrapopliteal bypass grafts. Methods We gathered data from a registry of catheter-based procedures for peripheral artery disease. Of 1554 arteriograms performed from 2006 to 2012, 30 patients had interventions for failing bypass vein grafts to infrapopliteal target vessels. The first intervention for each patient was used in this analysis. Duplex ultrasonography was used within… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…The median interval from bypass to first endovascular intervention was 5 months (range, 1-46 months) and did not vary significantly when stratified by site of lesion (inflow lesions, 7 [range, [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]; proximal anastomosis lesions, 9 [range, 2-24]; vein graft lesions, 8.5 [range, 2-37]; distal anastomosis lesions, 6 [range, 1-47]; outflow lesions, 4 [range, 1-36]; P ¼ .37). Operative interventions occurred significantly earlier at a median of 1 months (range, 1-14 months) after bypass when compared with endovascular interventions (P ¼ .007).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The median interval from bypass to first endovascular intervention was 5 months (range, 1-46 months) and did not vary significantly when stratified by site of lesion (inflow lesions, 7 [range, [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]; proximal anastomosis lesions, 9 [range, 2-24]; vein graft lesions, 8.5 [range, 2-37]; distal anastomosis lesions, 6 [range, 1-47]; outflow lesions, 4 [range, 1-36]; P ¼ .37). Operative interventions occurred significantly earlier at a median of 1 months (range, 1-14 months) after bypass when compared with endovascular interventions (P ¼ .007).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, another study found that only 37% of the patients were free from graft restenosis at 12 months and 31% at 24 months after the first intervention, although again with good technical success and low overall morbidity. 16 As such, we feel that endovascular therapy should be considered the first-line treatment of threatened grafts if suitable. Surgical graft salvage remains an option in selected patients after failed endovascular interventions, although in our series this was necessary in only 11% of grafts.…”
Section: Discussionmentioning
confidence: 98%
“…Similar results have been reported by others. 7,9 To maintain patency of the failing grafts, multiple EVTs are required frequently. In this study, EVT was performed a median of two times and maximum of 11 times.…”
Section: Discussionmentioning
confidence: 99%
“…9 Westin et al reported that their first EVT was performed a median of 12 months after infrapopliteal bypass (range 4e45 months). 7 Such an early intervention indicates that some vein grafts fail early after distal bypass, and that early detection of the failing grafts leads to early EVT.…”
Section: Discussionmentioning
confidence: 99%
“…There are now many new devices for the interventional therapy of vascular lesions causing CLI. The evidence is still not robust but in specialized institutions some of the devices are already an indispensable part of the interventional armamentarium, making therapies faster and safer than before [290,[358][359][360][361].…”
Section: Bmentioning
confidence: 99%